2021
DOI: 10.1002/ejlt.202000088
|View full text |Cite
|
Sign up to set email alerts
|

Front Face Fluorescence Spectroscopy Combined with PLS‐DA Allows to Monitor Chemical Changes of Edible Vegetable Oils during Storage at 60 °C

Abstract: In this work, front‐face fluorescence spectroscopy coupled with chemometric tools are used for the monitoring of rapeseed, sunflower, extra virgin olive, and linseed oil. The oil samples are heated at 60 °C for up to 15 days. The fluorescence excitation spectra are scanned in the range of 270–420 nm and 250–310 nm after emission wavelength set at 450 and 330 nm, respectively. The primary and secondary lipid oxidation products are also determined on the same oil samples. By applying partial least square discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…A very recent study that was conducted by Botosoa et al [ 89 ] focused on the study of rapeseed, sunflower, extra virgin olive and linseed oils. Front-face fluorescence spectroscopy coupled with PLS-DA were applied.…”
Section: Chemometric Application In Studies Related To Lipid Changes ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study that was conducted by Botosoa et al [ 89 ] focused on the study of rapeseed, sunflower, extra virgin olive and linseed oils. Front-face fluorescence spectroscopy coupled with PLS-DA were applied.…”
Section: Chemometric Application In Studies Related To Lipid Changes ...mentioning
confidence: 99%
“…The authors concluded that chemometric analysis with PLS-DA provided a successful discrimination of the samples regarding botanical type during storage, good differentiation of linseed oil and, to some extent, that of the rapeseed samples, based on ripening and exposure or not to air (uncapped or capped flasks, respectively), and during heating throughout storage, there was more stability of the sunflower and extra virgin olive oils compared to the linseed and rapeseed samples. The importance of this study is that the model produced can be extrapolated at an industrial level to monitor the oxidation of oils in a non-destructive way [ 89 ].…”
Section: Chemometric Application In Studies Related To Lipid Changes ...mentioning
confidence: 99%
“…For that reason, spectroscopic techniques are pointed out as a promising alternative, rapid and green analysis, to carry out in situ studies where a global and dynamic perspective of the VOO degradation state can be acquired. Previous studies , verified the applicability of the Fourier transform infrared (FTIR) accessory called mesh cell to track the chemical degradation of VOO through the monitoring of the intensity of the band assigned to different oxidation products, , which are interpreted as oxidation markers.…”
Section: Introductionmentioning
confidence: 99%